Tualang Honey prevents neuronal damage in medial prefrontal cortex (mPFC) through enhancement of cholinergic system in male rats following exposure to normobaric hypoxia (Bangladesh Journal of Medical Science, 2021)
Background: Medial prefrontal cortex (mPFC) is considered to be involved in human cognition to mPFCin terms of learning and memory. Hypoxia is one of the crucial factors causing secondary damage incerebral hemorrhage and traumatic brain injury. However, the underlying mechanisms and possibletherapeutic approach to prevent neuronal damage has not been attempted yet. Therefore, the present studyaimed to investigate the role of Tualang honey on medial prefrontal cortical neuronal morphology andcholinergic markers such as acetylcholine (ACh) and acetylcholinesterase (AChE) following exposure to normobaric hypoxia in rats.Material and methods: Adult male Sprague-Dawley rats were dividedinto four groups: (i) sucrose treated non-hypoxia, (ii) sucrose treated hypoxia, (iii) Tualang honeytreated non-hypoxia and (iv)Tualang honey treated hypoxia. Rats received sucrose (1 mL of 7.9%) andTualang honey (0.2 g/kg), respectively, for 2 weeks prior to hypoxia exposure. Morphological study wasperformed by using Nissl staining and cholinergic markers were estimated by ELISA technique.Resultsand discussion: Sucrose treated hypoxia group showed significantly lower mean ACh and higher meanAChE concentrations (P